World of religions - Samarpan (New Delhi, 2018)
Every religion is the product of the spiritual realisations of some of the greatest human minds, the likes of whom rarely walk on this earth. Religion becomes a unifying force when it focusses on the enlightening thoughts preached by these men; however, it tends to become disruptive when it depends on the limited knowledge of ordinary people to interpret them. The World of Religions presents eight major religions of the world and discusses their origin, growth and their impact on society. The chapters reveal the greatness of every religion, all of whom aspire to integrate purity, compassion and peace in everyday life.
Keywords: Religions